Faisons un rêve Based on a Play by Sacha Guitry - Guitry, Sacha; Benoit, Georges; Raimu; Delubac, Jacqueline (Sacha Guitry: L'âge d'or (1936-1938), 2012)
"Faisons un rêve" is a typical boulevard comedy originally written and played for the theatre before it was turned into a film. With its cramped cast, the film is a delightful piece of comedy on one of the most classical themes, that of a shrewd and mouthy lady-killer (Sacha Guitry) seducing a charming wife (Jacqueline Delubac) away from her stereotyped doltish husband (Raimu). [shakscreen.org]